2022
DOI: 10.3389/fonc.2022.967207
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis-associated long noncoding RNAs can predict prognosis and differentiate between cold and hot tumors in ovarian cancer

Abstract: ObjectiveThe mortality rate of ovarian cancer (OC) is the highest among all gynecologic cancers. To predict the prognosis and the efficacy of immunotherapy, we identified new biomarkers.MethodsThe Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression Project (GTEx) databases were used to extract ovarian cancer transcriptomes. By performing the co-expression analysis, we identified necroptosis-associated long noncoding RNAs (lncRNAs). We used the least absolute shrinkage and selection operator (LASSO) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Zhu et al built an eight necroptosis-related lncRNAs signature with significant values in predicting prognostic in OC [ 35 ]. Besides, Yi-Bo He et al applied six necroptosis-associated lncRNAs to construct a model, which was used to differentiate between hot and cold tumors and provide the treatment strategy for OC [ 36 ]. These studies suggested that necroptosis-related lncRNA signature could perform well in predicting prognosis in OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al built an eight necroptosis-related lncRNAs signature with significant values in predicting prognostic in OC [ 35 ]. Besides, Yi-Bo He et al applied six necroptosis-associated lncRNAs to construct a model, which was used to differentiate between hot and cold tumors and provide the treatment strategy for OC [ 36 ]. These studies suggested that necroptosis-related lncRNA signature could perform well in predicting prognosis in OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the six survival-related lncRNAs, AC090559.1 demonstrated its prognostic value in various programmed cell death [ 41 44 ]. AL133371.2 can also predict the prognostic of autophagy-related and necroptosis-related survival in different cancers [ 45 , 46 ]. LINC01094 was known for their regulatory function in glioblastoma and ovarian cancer [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is a new type of cell death regulation whose morphological characteristics are similar to those of necrosis, but the difference lies in whether it is regulated by signaling pathways (37). Recent studies have shown that necroptosis is closely associated with tumor progression (38)(39)(40)(41), but little is known about the role of necroptosis in ccRCC. In this study, we characterized the expression of necroptosis-related genes, established an NRL model to predict OS, and evaluated its predictive power in terms of clinical outcomes, immunologic microenvironments, and response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%